2015
DOI: 10.1002/jhet.2369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Some Novel Hydrazide, Pyrazole, Triazine, Isoxazole, and Pyrimidine Derivatives

Abstract: In continuation of our efforts to find a new class of antimicrobial agents, a series of pyrazole, 1,2,4‐triazine, isoxazole, pyrimidine, and other related products containing a hydrazide moiety were prepared via the reaction of 2‐cyano‐N‐((2‐methoxynaphthalen‐1‐yl)methylene) acetohydrazide (1) with appropriate chemical reagents. These compounds were evaluated for their antimicrobial activities, and also their minimum inhibitory concentration against most of test organisms was performed. Among the tested compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…11-13 illustrate FT-IR spectra of pure inhibitors liquid and the layer formed on carbon steel samples aer putting in 1.0 M HCl for a day in the presence of 20 Â 10 À6 M of (H4) when comparing the spectra of inhibitor solution with the spectra of the carbon steel surface aer immersion, the two spectra have the same properties, which mean that the compounds were adsorbed on the carbon steel surface. 18 The obtained results illustrate the mechanism of interference between (H4 & H5 & H6) and carbon steel surface. The shiing and missing in the spectra aer immersion showed that the interaction between (H4 & H5 & H6) and carbon steel surface was happened through functional groups mentioned in Table 9.…”
Section: Ft-ir Spectroscopy Analysismentioning
confidence: 66%
See 1 more Smart Citation
“…11-13 illustrate FT-IR spectra of pure inhibitors liquid and the layer formed on carbon steel samples aer putting in 1.0 M HCl for a day in the presence of 20 Â 10 À6 M of (H4) when comparing the spectra of inhibitor solution with the spectra of the carbon steel surface aer immersion, the two spectra have the same properties, which mean that the compounds were adsorbed on the carbon steel surface. 18 The obtained results illustrate the mechanism of interference between (H4 & H5 & H6) and carbon steel surface. The shiing and missing in the spectra aer immersion showed that the interaction between (H4 & H5 & H6) and carbon steel surface was happened through functional groups mentioned in Table 9.…”
Section: Ft-ir Spectroscopy Analysismentioning
confidence: 66%
“…The investigated compounds were synthesized as described before 18,19 and are listed in Table 1. All the structures of the prepared compounds were elucidated by elemental analysis 1 H-NMR, 13C -NMR, and mass spectral data.…”
Section: Preparation Of Inhibitorsmentioning
confidence: 99%
“…From in vitro test, it was found that compound (54-57) exhibited substantial inhibitory activity against bacterial strains with inhibition zone diameter within 15-24 mm. Refat and Fadda reported the synthesis and antimicrobial activity of some novel hydrazide, pyrazole, triazine, isoxazole, and pyrimidine derivatives [72]. Surprisingly, pyrazole (58) was denoted as the most potent compound within this research result.…”
Section: Fig 4: Structure Of Compounds (48-60)mentioning
confidence: 76%
“…A novel class of 3-(benzofuran-2-yl)-5-(4-methoxyphenyl)-4,5-dihydro-1H-pyrazole derivatives was designed by Rangaswamy et al [80]. Using well plate method for antimicrobial assay, compound (72) and (73) exhibited good inhibitory activity against E. coli, S. aureus, and P. aeruginosa.…”
Section: Research In 2017mentioning
confidence: 99%
“…According to the MS of compound 12, the m/z was 371 corresponding to its molecular formula C 16 Next, the synthetic potency and applicability of cyanoacetamide derivative 1 were investigated to develop a facile and convenient route to some novel pyrazole and pyridine derivatives with an anticipated wide spectrum of bioresponses. 31,32 Thus, the Knoevenagel condensation of 1 with aromatic aldehydes, namely piperonal, vanilline, and 4-N,N-dimethylbenzaldehyde, in reuxing ethanol using piperidine as a basic catalyst afforded the corresponding arylidene derivatives 16a-c. Treatment of 16c with hydrazine hydrate in boiling ethanol yielded 3-amino- (17).…”
Section: Chemistrymentioning
confidence: 99%